DNA Copy Number Control Through Inhibition of Replication Fork Progression - Nordman, Jared T. (Cell Rep, 2014)
Proper control of DNA replication is essential to ensure faithful transmission of genetic material and to prevent chromosomal aberrations that can drive cancer progression and developmental disorders. DNA replication is regulated primarily at the level of initiation and is under strict cell cycle regulation. Importantly, DNA replication is highly influenced by developmental cues. In Drosophila, specific regions of the genome are repressed for DNA replication during differentiation by the SNF2 domain-containing protein SUUR through an unknown mechanism. We demonstrate that SUUR is recruited to active replication forks and mediates repression of DNA replication by directly inhibiting replication fork progression instead of functioning as a replication fork barrier. Mass-spec identification of SUUR associated proteins identified the replicative helicase member CDC45 as a SUUR-associated protein, supporting a role for SUUR directly at replication forks. Our results reveal that control of eukaryotic DNA copy number can occur through inhibition of replication fork progression.